'Let's Just Wait One More Day': Impact of Timing on Surgical Outcome in the Treatment of Adhesion-Related Small Bowel Obstruction. Issue 2 (February 2013) - Joseph, Sigi P.; Simonson, Mike; Edwards, Christopher
Controversy exists but most surgeons agree that surgical treatment for failed conservative management of adhesion-related small bowel obstruction (SBO) should be within 48 hours. However, many find themselves delaying definitive treatment in the hopes of resolution. Our aim was to determine what impact timing has on surgical outcomes of SBO. A retrospective review of all consecutive patients surgically treated for adhesion-related SBO was performed from January 2001 to August 2006. Study groups included patients treated emergently (less than 6 hours), ex-peditiously (6 to 48 hours), and delayed (greater than 48 hours). Laparoscopic, open, and converted treatment types were controlled for as confounding variables using analysis of variance. Outcome measures were return of bowel function after surgery (RBF), length of stay after surgery (LOS), and morbidity. There were 27 emergencies, 30 treated expeditiously, and 34 delayed. Groups were matched in age and gender. RBF after surgery was significantly longer for those delayed in treatment compared with those treated expeditiously (greater than 48 hours = 7.4 days vs less than 6 hours = 7.6 and 6 to 48 hours = 5.4; P < .05) as well as LOS after surgery (greater than 48 hours = 12.3 days vs less than 6 hours = 10.1 and 6 to 48 hours = 7.6; P < 0.05). Patients treated with laparoscopy within 6 to 48 hours had a significantly shorter RBF and LOS than any other combination of timing and treatment. Postoperative morbidity was higher in the delayed group (79%) than the other groups (44% emergent and 40% expeditious) ( P < 0.05). There was one death in the delayed group. Delaying surgical treatment beyond 48 hours for SBO is common and results in worse outcomes and longer LOS. Laparoscopic treatment within 48 hours is superior to open treatment.